Brain Atrophy Following Deep Brain Stimulation: Management of a Moving Target. (21st October 2020) - Chiu, Shannon Y.; Deeb, Wissam; Zeilman, Pamela; Ramirez-Zamora, Adolfo; Patterson, Addie; Patel, Bhavana; Foote, Kelly D.; Okun, Michael S.; Patel, Amar; Almeida, Leonardo
Clinical vignette: A 51-year-old man with essential tremor (ET) had bilateral ventralis intermedius nucleus deep brain stimulation (VIM-DBS) placed to address refractory tremor. Despite well-placed DBS leads and adequate tremor response, he subsequently experienced worsening. Re-programming of the device and reconfirming the electrical thresholds for benefits and side effects were both performed. Six years following DBS implantation, repeat imaging revealed brain atrophy and a measured lead position change with a coincident change in clinical response. Clinical dilemma: What do we know about brain atrophy affecting lead placement and long-term DBS effectiveness? What are the potential strategies to combat narrowed therapeutic thresholds and to maximize DBS therapeutic benefit? Clinical solution: Decreasing the electrical field of stimulation and programming in a bipolar configuration are strategies to provide symptomatic tremor control and to minimize stimulation-induced side effects. Gaps in knowledge: Currently, effects of brain atrophy, and factors underpinning emergence of side effects and/or loss of benefit in chronic VIM-DBS remain largely unexplored.